CASK, APBA1, and STXBP1 collaborate during insulin secretion. (15th January 2021) - Zhang, Kai; Wang, Tianyuan; Liu, Xingjing; Yuan, Qingzhao; Xiao, Tin; Yuan, Xiangjiang; Zhang, Yijian; Yuan, Li; Wang, Yao
Abstract: Calcium/calmodulin-dependent serine protein kinase (CASK) knockdown reduces insulin vesicle docking to cell membranes. Here, we explored CASK interactions with other proteins during insulin secretion. Using co-immunoprecipitation, liquid chromatography-mass spectrometry and bioinformatic analysis, we identified that CASK, Adapter protein X11 alpha (APBA1), and Syntaxin binding protein 1 (STXBP1) formed tripartite complex during insulin secretion. CASK enhanced APBA1–STXBP1 interaction and mediated their traffic from cytoplasm to plasma membrane during insulin release. High fatty acid stimulation decreased insulin secretion along with CASK, APBA1, and STXBP1 expression; Cask overexpression enhanced CASK/APBA1/STXBP1 tripartite complex function, and may thereby rescue lipotoxicity-induced insulin-release defects. Collectively, our results illustrated the function of CASK in insulin granules exocytosis, which broadens the underlying mechanism of insulin secretion and highlights the clinical potential of CASK as a drug target of type 2 Diabetes Mellitus (T2DM). Highlights: CASK/APBA1/STXBP1 form a tripartite complex during insulin secretion. CASK mediates APBA1 and STXBP1 traffic from the cytoplasm to the plasma membrane. Impaired CASK/APBA1/STXBP1 tripartite complex cause insulin secretion defects. Overexpression of CASK could rescue lipotoxicity-caused insulin release defects.